Immunological dysfunction in chronic arsenic exposure: From subclinical condition to skin cancer. Issue 11 (25th August 2018) - Yu, Sebastian; Liao, Wei‐Ting; Lee, Chih‐Hung; Chai, Chee‐Yin; Yu, Chia‐Li; Yu, Hsin‐Su
Abstract: Exposure to arsenic is a global health issue. Long‐term arsenic exposure may associate with various cancers and many other pathological effects. Over 100 million people worldwide are exposed to arsenic particularly in countries such as Bangladesh, Chile, China, India, Mexico, Taiwan and the USA. Drinking of water contaminated with arsenic is the major route of human exposure. Skin lesions are considered to be the most common adverse effects associated with chronic arsenic exposure. Skin lesions usually develop with the latency period spanning more than 20 years from first exposure. Arsenic‐induced Bowen's disease, the most frequently encountered carcinoma in situ resulting from chronic arsenic exposure, is characterized by multiple and recrudescent lesions. Long‐term arsenic exposure results in impaired immunity in susceptible individuals. In the prenatal stage, enhanced placental inflammatory responses and reduced placental T cells by arsenic may result in decreased thymic size and functions in newborns. In childhood, arsenic exposure may reduce peripheral CD4 + cells and interleukin‐2 secretion which leads to susceptibility to opportunistic infections. There was an impairment of macrophage function and oxidative DNA damage of peripheral polymorphonuclear leukocytes in adults with skin lesions. In arsenic‐induced Bowen's disease lesions, a decrease in the number and functions of Langerhans cells and, in parallel, a selective CD4 + cell apoptosis was noticed. These findings provide scientific evidence for understanding the phenomenon of arsenic‐induced immune escape in the early stage of carcinogenesis and a reasonable explanation for multiple and recrudescent arsenic cancers in the skin.